Importance of order filler tubes blood samples for nursing - Mª África Conde Anguita; Eduardo Mesa Fernández; Josefa Moral Jiménez (Fundación para el Desarrollo de la Enfermería, 2011)
The extraction of blood samples for laboratory analysis is a technique common in nursing practice. Quite often mistakes are made in the sampling involving the erroneous results and, sometimes, a rejection of the sample by the laboratory, resulting in a new extraction. It is the responsibility of professional nurses prevent, control and minimize errors. The method of blood sampling is important to have quality results. The order of blood filled tubes may alter some outcomes, that´s why it is necessary to know what the correct order of filling is. All this is intended to reduce the number of rejected samples, avoiding the risk of misinterpretation in the diagnosis of patients and the inconvenience caused to patients by repeated laboratory tests.